Biochemical Markers in Patients with Mild and Severe Covid-19 Infection - Shalini Maksane; Megha Bangar; Supriya Khillare; Anita Chalak; Milind Nadkar (Dr. Annil Mahajan, 2021)
Background: The 2019 novel coronavirus disease (COVID-19) is the greatest public health problem to date as number of COVID-19 patients are dramatically increasing worldwide. Clinical criteria are susceptible to subjective and objective factors, which may lead to an extended time for diagnosing and the possibility of misdiagnosing severe COVID-19. Therefore, it makes sense to find a potential biomarker that could effectively diagnose severe COVID-19. Objective: To study biochemical markers in mild and severe patients of covid-19 infection. Material and Methods: This observational study was conducted in the Department of Biochemistry, Seth G S Medical College and KEM Hospital, a tertiary care hospital of Mumbai. Our study included COVID-19 positive patients diagnosed for COVID-19 based on the results of RT-PCR conducted at our centre. Patients were categorized into 2 groups mild (n-50) and severe (n-50) on the basis of severity of clinical presentation, each between 18-80 yrs. of age. Biochemical parameters were compared between these two groups and various biochemical parameters was evaluated using unpaired t-test. Results: The biochemical markers were compared in group-1 and group-2. Group-2 patients had significantly higher levels of serum LDH (p=0.0001), CRP (p=0.0001), BUN (p= 0.007), serum creatinine (p=0.0001), serum AST (p=0.02) and serum ALT (p=0.02). Conclusion: The biomarkers studied in the present research work, if considered together provide a brief overview on the most frequent laboratory abnormalities encountered in patients with COVID-2019 infection which might be useful in indicating progression from mild to severe disease.